Effect of different levels of palm oil inclusion in diet on growth performance, biochemical parameters and carcass characteristics of slow growing broilers in tropical environment - Gname, Kolani Ali Yendou-; Amoussa Modukpè Romziath; Ahmed, Mijiyawa; messan, Agboka Jacques kossi-; wéré, Pitala (Central Research Institute For Agriculture, 2024)
The study aimed to evaluate the growth performance, biochemical parameters and carcass characteristics of slow-growing Dutch blue broilers in a tropical environment over a period of 14 weeks. A total of 240, 14 – day old Dutch blue broilers were randomly assigned to four treatment groups (T0, T1, T2 and T3) and were fed diets containing 0%, 1%, 2% and 3% palm oil, respectively. Data were collected on feed intake, body weight, biochemical parameters, organs and carcass weight. The collected data were analyzed using GraphPad Prism version 8.0 software. The results showed that the feed intake of the broilers increased as the level of palm oil incorporation increased. The average daily gain was higher in groups T2 and T3 compared to the other groups. Feed conversion ratio was positively impacted by the inclusion of 1% and 2% palm oil in the diet. An increase in total cholesterol levels was observed as the level of palm oil inclusion increased, while the lowest concentrations of total protein and triglycerides were found in the group fed the control diet. With regards to carcass characteristics, the yields of breast meat, drumstick, and carcass increased as the level of palm oil inclusion in the diet increased. However, there was no significant effect on thigh yield (P > 0.05). The relative weight of the liver decreased significantly with of palm oil levels, while the relative weights of the spleen and heart remained similar (P > 0.05). The inclusion of 1% and 2% palm oil in the broiler feed improves feed efficiency, growth performance, and carcass yield.